High-Dose MTX110 (Soluble Panobinostat) Safely Administered into the Fourth Ventricle in a Nonhuman Primate Model. (16th November 2020) - Kharas, Natasha; Yu, Bangning; Janssen, Christopher; Trimble, Amanda; Ballester, Leomar; Patel, Rajan; Mohammad, Afroz; Elmquist, William; Sirianni, Rachael W; Sandberg, David I
Abstract: INTRODUCTION: New strategies are needed to treat medulloblastoma and other malignant tumors that originate in the posterior fossa in children. Systemic chemotherapy causes considerable toxicity and is often ineffective in a recurrent setting. Local delivery of chemotherapeutic agents directly into the fourth ventricle is a novel treatment approach. METHODS: Four rhesus macaque monkeys underwent posterior fossa craniectomy and catheter insertion into the fourth ventricle. In Group I (short-term group, n = 2), catheters were externalized and lumbar drain catheters were placed simultaneously to assess cerebrospinal fluid (CSF) distribution after short-term infusions. MTX110 (0.5 ml of 300 μM panobinostat solution) was infused into the fourth ventricle daily for five consecutive days. In Group II (long-term group, n = 2), fourth ventricle catheters were connected to a subcutaneously-placed port for subsequent long-term infusions. Four cycles of MTX110, each consisting of 5 daily infusions, were administered over 8 weeks. Animals underwent detailed neurological evaluations, MRI scans, and post-mortem histological analysis. RESULTS: No neurological deficits occurred after intraventricular MTX110 infusions. MRI scans showed catheter placement within the fourth ventricle in all 4 animals. There were no MRI signal changes in the brain in any animals. Histologically, the cytoarchitecture of the brain was preserved with only focal mild post-surgical changes in all animals. Serum panobinostat levels at two and four hours after infusion were undetectable in both groups. In Group I (short-term group), the mean peak panobinostat level in fourth ventricle CSF (6242 ng/ml) exceeded that in lumbar CSF (9 ng/ml) by greater than 600-fold. In Group II (long-term group), mean peak CSF panobinostat level (11, 042 ng/ml) was significantly higher than mean trough CSF level (33 ng/ml; P  < .0001). CONCLUSION: MTX110 (soluble panobinostat) can be safely infused in the fourth ventricle in non-human primates at high supra-therapeutic doses. Post-infusion CSF panobinostat levels peak immediately in the fourth ventricle and then rapidly decrease over 24 hours. These results provide background data for a recently opened pilot clinical trial in patients with recurrent medulloblastoma.